Using the Total Physical Response to Improve Students’ Vocabulary Mastery - Yuyun Bahtiar (SELL Journal : Scope of English Language Teaching, Linguistics, and Literature, 2017)
Vocabulary is important aspect of language that uses in communication. In Indonesia, English has been taught since in elementary school even just as local content subject. The background of the research is the low score of student’s vocabulary among fourth grade students of MI DARUL ULUM Widang – Tuban. The result of fourth grade students average score was 40.2. Total Physical Response with work book (LKS) and real object as media can improve fourth grade students’ vocabulary significantly. At the first cycle, the result of student average score was 54.1. Thus, the researcher changes the scenario of learning that used for the second cycle in order to the students easy to memorize the vocabulary taught, make all students active and enjoy learning activity. Average score after implementing the second cycle was significance improve become 100% and it means that the target was achieved. By using this method, the research found the advantages of the use of TPR such as the learning process becomes more enjoyable, the students find it easier to memorize the vocabulary taught, all students were active involved in teaching learning process, and both students and teacher enjoy teaching learning process.